Scalable Multi-Level Synchronization Technique of Distributed Multi-RFSoC-Server Systems for 6G - Karle, Christian; Neu, Marc; Nuss, Benjamin; Witte, Lukas; Scheder, André; Waldner, Eva; Shkurtaj, Ema; Harbaum, Tanja; Becker, Jurgen (International System on Chip Conference, 2024)
The new 6th generation (6G) standard promises increased data transmission rates and opens up entirely new application fields, such as joint-communication and sensing (JCAS). Modern high-performance multiple-input multiple-output (MIMO) systems with high bandwidth and channel count allow evaluation and testing of waveforms and algorithms in real-world scenarios. However, commercial off-the-shelf (COTS) MIMO systems are often costly and cannot be scaled to massive MIMO (mMIMO) systems without huge overhead. The ReLoDAQ system, based on combined radio frequency system-on-chip (RFSoC)-server architecture, offers a cost-effective and scalable solution for the development of a modern mMIMO system. However, this system is only scalable in terms of channel count and does not provide scalable synchronization and trigger mechanisms, which are essential for applications like JCAS or radar. In this paper, we present a scalable sample- and data-level synchronization and trigger mechanism to operate a mMIMO system based on the ReLoDAQ structure in a phase coherent manner. To achieve this, we extend the firmware of the RFSoCs with additional trigger and synchronization logic. Furthermore, we developed a scalable clock distribution network to distribute phase coherent clocks in the mMIMO system. Through measurements on an experimental mMIMO system consisting of two RFSoCs and four servers, we demonstrate that our approach enables phase coherent operation across all channels in the mMIMO system based on the cost-efficient and scalable ReLoDAQ architecture.
CRIS-Team Scopus Importer:2024-12-13
Keywords: 6G; clock distribution; mMIMO; RFSoC; synchronization